Shaping Educational Strategies: A Literature Review on Uncertainty and the Unexpected - Lorenza Maria Capolla (Education Sciences, 2024)
A key feature of contemporary times is the high degree of complexity that impacts all spheres and aspects of today’s society, particularly within education. This complexity, deriving from a postdigital world in a polycrisis, causes continuous eventualities and results in these conditions of uncertainty. This contribution reviews the present literature on the issues of the unexpected and uncertainty. From the 13 articles included in the review, an attempt is made to define the terms “uncertainty” and “unexpected” in order to scan the management strategies proposed by various authors in diverse fields, highlighting the correlation between uncertainty, the unexpected, and anxiety. Although this review revealed a lack of a universal definition of the “unexpected” and “uncertainty”, the analysis seems to have revealed some common and essential features in various articles and perspectives on the topic. Suggestions drawn from the analysis prove particularly useful in investigating the implications that uncertainty and the unexpected have in education, especially in training future teachers.